2019
DOI: 10.1186/s13048-019-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis impact of hyperthermic intraperitoneal chemotherapy (HIPEC) plus cytoreductive surgery (CRS) in advanced ovarian cancer: the meta-analysis

Abstract: Background and objective Previous studies about the prognostic value of the HIPEC have yielded controversial results. Therefore, this study aims to assess the impact of HIPEC on patients with ovarian cancer. Results We included 13 comparative studies, and found that the overall survival (OS) and progression-free survival (PFS) in HIPEC groups were superior to groups without HIPEC treatment in the all total population (HR = 0.54,95% CI:0.45 to 0.66, HR = 0.45, 95% CI: 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 30 publications
(23 reference statements)
4
38
0
3
Order By: Relevance
“…Two prospective case-control studies concluded that the treatment was feasible and safe in the primary setting, but they were not able to draw conclusions on survival outcomes. 40 This meta-analysis confirms the finding in the OVHIPEC trial that the addition of HIPEC to surgery does not increase toxicity. 39 A recent meta-analysis including randomized controlled trials and case-control trials showed better outcomes after treatment with surgery and HIPEC in patients with primary advanced ovarian cancer (pooled HR for OS, 0.54; 95% CI, 0.45-0.66; pooled HR for PFS, 0.45; 95% CI, 0.32-0.62).…”
Section: Existing Evidencesupporting
confidence: 78%
See 1 more Smart Citation
“…Two prospective case-control studies concluded that the treatment was feasible and safe in the primary setting, but they were not able to draw conclusions on survival outcomes. 40 This meta-analysis confirms the finding in the OVHIPEC trial that the addition of HIPEC to surgery does not increase toxicity. 39 A recent meta-analysis including randomized controlled trials and case-control trials showed better outcomes after treatment with surgery and HIPEC in patients with primary advanced ovarian cancer (pooled HR for OS, 0.54; 95% CI, 0.45-0.66; pooled HR for PFS, 0.45; 95% CI, 0.32-0.62).…”
Section: Existing Evidencesupporting
confidence: 78%
“…39 A recent meta-analysis including randomized controlled trials and case-control trials showed better outcomes after treatment with surgery and HIPEC in patients with primary advanced ovarian cancer (pooled HR for OS, 0.54; 95% CI, 0.45-0.66; pooled HR for PFS, 0.45; 95% CI, 0.32-0.62). 40 This meta-analysis confirms the finding in the OVHIPEC trial that the addition of HIPEC to surgery does not increase toxicity. 18,32,41 A Korean study group presented preliminary results of a randomized trial at the 2017 American Society of Clinical Oncology annual meeting.…”
Section: Existing Evidencesupporting
confidence: 78%
“…HIPEC has improved survival outcomes for patients with PM from various primary tumors. [1][2][3][4][5][6][7] This potential survival benefit needs to be in balance with the associated risks of treatment-related morbidity and mortality. HIPEC surgeons attempt to make this estimation for their patients in advance of planning a CRS ?…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques are used to achieve local-regional hyperthermia (LRHT), all of which have the end goal of the destruction of the tumor. Techniques that have been developed to achieve this include: infrared water-window (IR-A); ( 61 , 62 ) Hyperthermic Intraperitoneal Chemotherapy ( 63 , 64 ), [HIPEC: heating the abdominal organs using a warm chemo solution applied during open surgery ( 65 ) or laparoscopic surgery ( 66 )] and High-intensity focused ultrasound [HIFU, for deep non-invasive heating ( 67 , 68 )]. Photodynamic therapy (PDT) and its different versions are local energy-absorption applications which use the activation of a photosensitizer by the appropriate light dose (usually using a laser-beam in a minimally invasive way) ( 69 ).…”
Section: Local and Regional Hyperthermiamentioning
confidence: 99%